An acoustic wave sensor for the hydrophilic fluoride - Valente, Nuno I. P. (2019)
A new acoustic wave sensor to detect and quantify fluoride, one of the most hydrophilic anions, is proposed. Meso-octamethylcalix[4]pyrrole (OMCP) and seven of its derivatives were evaluated as piezoelectric quartz crystal coatings. Some of these sensors experienced appreciable coating leaching under a water flow, while others did show a very small sensitivity to fluoride. As the OMCP-naphthoquinone sensor was very sensitive to fluoride and did not lose a significant amount (α = 0.05) of coating during eight weeks, it was selected among all the others. A piezoelectric crystal coated with an amount of OMCP-naphthoquinone that produced a frequency decrease of 22 kHz showed a linear calibration range that extended up to 80 mg L−1, within which sensitivity to fluoride was 0.45 Hz L mg−1, and was able to detect fluoride at the concentration of 3.66 mg L−1. This sensor was used to determine fluoride in commercial fluoride tablets, and the result found was not statistically different (α = 0.05) from the value provided by the manufacturer.